The Very Best of Me: Longitudinal Associations of Perfectionism and Identity Processes in Adolescence. Issue 5 (7th July 2021) - Negru‐Subtirica, Oana; Pop, Eleonora Ioana; Damian, Lavinia E.; Stoeber, Joachim
Abstract : Personality and identity formation are intricately linked in adolescent development. The personality disposition of perfectionism has been associated with identity processes, but their longitudinal interplay in adolescence has not yet been investigated. This four‐wave study, with 5‐ to 6‐month intervals between each wave ( N = 744 Caucasian adolescents, M age = 15.2 years, 55% girls), examined associations between perfectionism (self‐oriented and socially prescribed) and identity processes in the domain of future plans. Self‐oriented perfectionism predicted increases in commitment making, identification with commitment, and exploration in depth. Socially prescribed perfectionism showed bidirectional positive relations with ruminative exploration. Exploration in depth predicted increases in socially prescribed perfectionism. Findings suggest that perfectionism is an important personality disposition in adolescent identity formation unfolding over time.